1968
DOI: 10.1002/tera.1420010106
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of cleft lip and its relation to embryonic face shape in A/J and C57BL mice

Abstract: A comparison was made of early face embryology in the inbred A/J mouse strain with a spontaneous frequency of about 12% cleft lip and the C57BL/6J strain which virtually never has cleft lip. From the time of their appearance the medial nasal, lateral nasal and maxillary processes are connected by an isthmus. Subsequently there is fusion between the adjacent epithelia of medial and lateral nasal processes. Failure of this fusion, followed by breakdown of the isthmus, results in cleft lip. Just before and when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0
1

Year Published

1977
1977
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 12 publications
5
84
0
1
Order By: Relevance
“…4 in Senders et al, 2003). Studies in mouse embryos showed that fusion between the nasal processes occurred initially at the posterior part of the nasal pits and proceeded in an anterior direction (Trasler, 1968;Gaare and Langman, 1977a), similar to what Hinrichsen described for human embryonic face development (Hinrichsen, 1985).…”
Section: Morphogenesis Of the Upper Lipsupporting
confidence: 76%
See 4 more Smart Citations
“…4 in Senders et al, 2003). Studies in mouse embryos showed that fusion between the nasal processes occurred initially at the posterior part of the nasal pits and proceeded in an anterior direction (Trasler, 1968;Gaare and Langman, 1977a), similar to what Hinrichsen described for human embryonic face development (Hinrichsen, 1985).…”
Section: Morphogenesis Of the Upper Lipsupporting
confidence: 76%
“…Recently, Senders et al (2003) presented high resolution SEM pictures of developing cynomolgus monkey embryonic faces. Comparing these with other histological and SEM studies of facial development in mouse and chick (Trasler, 1968;Gaare and Langman, 1977a,b;Yee and Abbott, 1978;Millicovsky and Johnston, 1981;Millicovsky et al, 1982;Trasler and Ohannessian, 1983;Cox, 2004) provides an accurate understanding of the morphological processes involved in facial development.…”
Section: Morphogenesis Of the Upper Lipmentioning
confidence: 76%
See 3 more Smart Citations